2017
DOI: 10.1017/s0025315417001321
|View full text |Cite
|
Sign up to set email alerts
|

Resource partitioning by two syntopic sister species of butterflyfish (Chaetodontidae)

Abstract: Resource partitioning is considered one of the main processes driving diversification in ecological communities because it allows coexistence among closely related and ecologically equivalent species. We combined three complementary approaches, i.e. the evaluation of foraging behaviour, diet composition and nutritional condition (RNA:DNA ratio), to assess feeding by two closely related (sister) butterflyfishes that are syntopic in Puerto Rico. Chaetodon capistratus had a higher abundance and higher bite rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The findings indicated that food item partitioning occurs among the four study species, with S. unimaculatus , S. virgatus , and S. puellus in particular showing clear differences in the food items taken without any evidence of habitat partitioning. Such food item partitioning among species of the same genus has also been found in other families (Nanami & Shimose, 2013; Brandl, William & Bellwood, 2015; Liedke et al, 2017).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The findings indicated that food item partitioning occurs among the four study species, with S. unimaculatus , S. virgatus , and S. puellus in particular showing clear differences in the food items taken without any evidence of habitat partitioning. Such food item partitioning among species of the same genus has also been found in other families (Nanami & Shimose, 2013; Brandl, William & Bellwood, 2015; Liedke et al, 2017).…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have also demonstrated that species-specific food item and foraging substrate (i.e., feeding microhabitat) partitioning enable the coexistence of diverse fish species in the absence of distinct habitat partitioning (Gradfelter & Johnson, 1983; Bouchon-Navaro, 1986; Pratchett, 2005; Liedke et al, 2017). In some cases, the morphological characteristics of a species (e.g., body shape, dentition type, and jaw-lever mechanics) affect this partitioning among syntopic species (Carpenter, 1996; Nanami & Shimose, 2013; Brandl, William & Bellwood, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Butterflyfish food choices provide an intriguing contrast to the similar sets of species eaten by congeneric spongivores, as their foraging patterns have often demonstrated resource partitioning among closely related species, especially in the highly diverse tropical western Pacific fauna (Lawton et al 2012, Pratchett 2014, Slattery and Gochfeld 2016). Resource partitioning was also demonstrated for two congeneric Caribbean butterflyfishes (Liedke et al 2018), while another pair of Caribbean congeners was shown to differ in ways reminiscent of the differences between sponge‐feeding by angelfishes vs. parrotfishes, with one species, Chaetodon capistratus , actively broadening its diet and the congeneric C. aculeatus feeding selectively on relatively hidden prey (Birkeland and Neddeker 1981).…”
Section: Discussionmentioning
confidence: 92%
“…The response variable is the presence of the bird in the perch (1 = used perch / 0 = unused perch). This way, with CLR we model the probability of a bird selecting a perch in relation with other available perches depending on the effect of the explicative variables (artificial/natural perch, height, distance to water and vegetation cover) in the same probabilistic process (Liedke et al 2018. We used the function clogit of the package 'survival' (Therneau 2015) of R (R Core Team 2018).…”
Section: Statistical Analysesmentioning
confidence: 99%